Double malignancies: a clinicopathological and outcomes retrospective analysis from a tertiary cancer referral centre in South India - Nandennavar, Manjunath I.; Angadi, Veerendra; Karpurmath, Shashidhar V.; Jacob, Roshan (International Journal of Research in Medical Sciences, 2019)
Background: The presence of second synchronous or metachronous primary malignancies in a cancer patient is not a rare phenomenon. Our study is an endeavour to present data on the frequency, types, and outcomes of double primary malignancies in Indian cancer patients. Methods: This was a retrospective study conducted in 28 cancer patients diagnosed with histologically confirmed double malignancy. Retrospective data of the cancer site, patient’s age at the presentation, gender, type of cancer (synchronous/metachronous), treatment, and outcome were recorded from patients presented with double malignancies from January 2012 to January 2019. Results: Among 28 patients (18 females; 10 males) with multiple primary malignancies, 10 (35.7%) and 18 patients (64.3%), respectively, had synchronous and metachronous primary malignancies. Overall, breast, gynecological, head, and neck cancer were the most common primary malignancies. Gastrointestinal tract, breast, and lung cancer emerged to be the most common second primary malignancy sites. Squamous cell carcinoma (SCC) and invasive ductal carcinoma (IDC) were the most common histopathological types of double malignancies. The majority of the patients received appropriate treatment for both the malignancies. Conclusions: Data from the present study clearly suggest that the occurrence of second primary malignancy is not rare in Indian cancer patients. The double malignancies can occur at any stage and for any type of cancer. Hence, we wish to highlight that the clinician should always be aware of the possibility of developing second malignancy either during evaluation or in follow up of a patient with malignancy.